2016
DOI: 10.1039/c6tc01032f
|View full text |Cite
|
Sign up to set email alerts
|

Role of various defects in the photoluminescence characteristics of nanocrystalline Nd2Zr2O7: an investigation through spectroscopic and DFT calculations

Abstract: Photoluminescence in the blue and green regions is observed for the first time in nanocrystals of Nd2Zr2O7 synthesized by gel combustion method. This emission is attributed to the presence of oxygen vacancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 75 publications
5
74
0
Order By: Relevance
“…Figure 3B Oxygen vacancies induced emission in blue and green regions have been observed previously from rare earth zirconate Gd 2 Zr 2 O 7 and Nd 2 Zr 2 O 7 . 28,29 To confirm the origin of the emission bands from the LZO and LHO NPs, they were further annealed in oxidizing and reducing atmospheres.…”
Section: Probing Observed Pl Differences Of Lzo and Lho Nps By Dft mentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 3B Oxygen vacancies induced emission in blue and green regions have been observed previously from rare earth zirconate Gd 2 Zr 2 O 7 and Nd 2 Zr 2 O 7 . 28,29 To confirm the origin of the emission bands from the LZO and LHO NPs, they were further annealed in oxidizing and reducing atmospheres.…”
Section: Probing Observed Pl Differences Of Lzo and Lho Nps By Dft mentioning
confidence: 99%
“…However, the literature pertaining to photoluminescence study in undoped La 2 B 2 O 7 (B = Zr and Hf) and their comparison is completely missing, though there have been reports for Nd 2 Zr 2 O 7 , Gd 2 Zr 2 O 7 , Y 2 Zr 2 O 7 , and Eu 2 Zr 2 O 7 . Eagleman et al observed blue emission in bulk La 2 Hf 2 O 7 powder induced by oxygen vacancies but could not assign the exact types of oxygen vacancies involved .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative low synthesis temperature: The processing temperature of the MSS method is relatively low compared to that required in a conventional solid-state reaction 26 or a sol-gel combustion reaction 27 . This lower temperature saves energy while producing high-quality NPs.…”
Section: Introductionmentioning
confidence: 99%